The Unconscious Dimensions of Second Language Acquisition: A Psychoanalytic Exploration of Memory, Affect and Linguistic Transformation - A.Mutharasi , A.Mutharasi; John, D. Wilfin (Journal of Neonatal Surgery, 2025)
Second language acquisition has traditionally been examined through cognitive, linguistic and sociocultural perspectives, while psychoanalytically informed psychological and affective processes shaping learners’ engagement with a second language remain comparatively underexplored. This study examines the unconscious dimensions of second language acquisition among postgraduate learners through a Freudian psychoanalytic framework, focusing on the interconnected roles of memory, affect, anxiety and linguistic transformation. Using a descriptive-correlational mixed-method design, the study was conducted among postgraduate students (N=50) at Manonmaniam Sundaranar University, Tirunelveli, Tamil Nadu. Quantitative data were collected through a structured Likert-scale questionnaire measuring observable affective and experiential indicators (memory, affect, anxiety and linguistic transformation), which were interpreted through a Freudian psychoanalytic framework rather than considered direct measures of unconscious processes. Qualitative data were obtained through semi-structured interviews and analyzed thematically through a psychoanalytic lens. The findings reveal statistically significant associations among affective experience, anxiety and perceived linguistic transformation. Affective security was positively associated with linguistic transformation, whereas language anxiety was negatively associated with learners’ perceptions of linguistic growth. Qualitative findings further revealed patterns related to early linguistic experiences, symbolic investment in English, emotional attachment to the mother tongue and the repetition of past classroom experiences in present language performance. Interpreted through Freudian concepts of repression, repetition compulsion and the return of the repressed, the study argues that second language acquisition is not merely a process of linguistic competence development but also a psychological negotiation involving memory, emotion and subject formation. The study contributes a psychoanalytic perspective to SLA research by foregrounding the affective, symbolic and subjective dimensions of language learning and suggesting the need for affect-sensitive approaches in multilingual educational contexts